Activity of Daily Living and Depressive Symptoms in Chinese Older Adults: A Latent Profile and Mediation Analysis - Peng Chen; Wenjian Xu (International Journal of Public Health)
ObjectivesThis study aims to examine vulnerable ADL-based subgroups of Chinese older adults, their links to depressive symptoms, and life satisfaction as a mediating factor.MethodsWe screened 8,211 participants aged 60 years and above who met the inclusion criteria from 2018 CHARLS. The different subgroups of ADL were identified by latent profile analysis. Life satisfaction and depressive symptoms were compared among the various ADL subgroups. Mediation analysis helped investigate the mediating role of life satisfaction between the various subgroups of ADL and depressive symptoms.ResultsTwo vulnerable subgroups of ADL were identified (Low Damaged class and High Damaged class), along with another subgroup of ADL (Not Damaged class), comprising the majority of Chinese older adults. The vulnerable subgroups of ADL had significantly lower life satisfaction and higher levels of depressive symptoms. The relationship between depressive symptoms and the vulnerable subgroups of ADL was partially mediated by life satisfaction.ConclusionThe results emphasize the role of life satisfaction in linking ADL with depressive symptoms, indicating potential areas for interventions to reduce depressive symptoms among older adults. This study is limited by its cross-sectional design precluding causal inference, reliance on self-reported data and unexplored moderating factors.